(untitled) (International journal of medical sciences, 2026)
This article assesses oral health-related quality of life in elderly patients requiring orthopedic rehabilitation using the validated OHIP-14 questionnaire. The survey was administered before prosthetic treatment and on day 33 after prosthesis placement. Within-group and between-group comparisons were performed, including total score dynamics and distribution across quality-of-life categories (“good”, “satisfactory”, “unsatisfactory”). The results demonstrated marked improvement after treatment, with a substantial decrease in total OHIP-14 scores in Groups 1 and 2, indicating a shift toward “good” quality of life. Group 3 also showed positive changes, although the magnitude of improvement was smaller and overall outcomes more frequently remained within the “satisfactory” range. The findings emphasize the clinical and psychosocial value of orthopedic rehabilitation in elderly patients.